A study on knowledge, attitude and practice (KAP) on infant and young child feeding practices (IYCF) of under two years children after implementation of Baal vita program (Sprinkles) in Raksirang VDC of Makwanpur district. - Kandel, Kamal Prasad (2011)
ABSTRACT: I have conducted research entitled'' A study on knowledge, Attitude and practice (KAP) 0n Infant and young child feeding practices (IYCF) of under two years children after implementation of Baal vita program (Sprinkles) In Raksirang VDC of Makwanpur district'', I have got the post graduate grant 2011 from Nepal health research council for the above mention research topic. Nepal is one of the developing Countries in the South Asia. Early childhood is very important and the crucial period for the proper physical, mental and emotional development. Therefore the child should be looked especially at this period in Nepal, child below two years are suffering from malnutrition the most. An improper feeding practice among young children particularly 6-23 months is a major cause of malnutrition. Thus, the present study has been focused on feeding practices of fewer than two years children. The study was quantitative study. Main objective of the study was to know the feeding practices of under two years children after implementation of Baal vita (Sprinkles) program in Raksirang VDC of Makwanpur district. Questionnaire were related to the Baal vita program, Breastfeeding practices and Complimentary feeding practices. Altogether 132 mothers were taken for the study. The structured questionnaire was developed, pretested and used to collect the information. After the collection of data, it was analyzed by using SPSS 17. Also, the data was presented in different table to make it more clear and specific. Among 132 of the respondent. Majority of the respondent were aged between 21-25 years. 37.885 mothers were illiterate and only 1.52% had secondary level education. Some of the respondents were pregnant before the age 20 years. One of the mother was give birth to her child at age of 15 years. 68.18% respondent had first Breastfed their child with in 1 house of birth. Colostrum feeding was seen not good. I have found still practice of squeezing colostrums. Current breastfeeding practice is seen good. About 88.64% of the respondent had started giving complementary food in correct time.